2009
DOI: 10.1088/0004-637x/696/1/841
|View full text |Cite
|
Sign up to set email alerts
|

Grain Growth and Density Distribution of the Youngest Protostellar Systems

Abstract: We present dust opacity spectral indexes (β) of the youngest protostellar systems (so-called Class 0 sources), L1448 IRS 2, L1448 IRS 3, and L1157, obtained between the λ = 1.3 mm and 2.7 mm continua, using the Combined Array for Research in Millimeter-wave Astronomy (CARMA). The unprecedented compact configuration and image fidelity of CARMA allow a better detection of the dust continuum emission from Class 0 sources, with a less serious missing flux problem normally associated with interferometry. Through vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
131
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(148 citation statements)
references
References 44 publications
16
131
1
Order By: Relevance
“…Such steep density profiles have been obtained previously toward more nearby protostars (Looney et al 2003;Chiang et al 2008Chiang et al , 2012Kwon et al 2009). The sources with flat visibility amplitudes appear similar to NGC 1333 IRAS 4B, a source with very flat visibility amplitudes out to ∼80 kλ (Looney et al 2003;Chiang et al 2008); this is equivalent to flat visibility amplitudes out to ∼150 kλ at the distance to Orion.…”
Section: Envelope Density Profilessupporting
confidence: 82%
“…Such steep density profiles have been obtained previously toward more nearby protostars (Looney et al 2003;Chiang et al 2008Chiang et al , 2012Kwon et al 2009). The sources with flat visibility amplitudes appear similar to NGC 1333 IRAS 4B, a source with very flat visibility amplitudes out to ∼80 kλ (Looney et al 2003;Chiang et al 2008); this is equivalent to flat visibility amplitudes out to ∼150 kλ at the distance to Orion.…”
Section: Envelope Density Profilessupporting
confidence: 82%
“…For OH5 dust, β = 1.75 over all submillimeter and millimeter wavelengths, implying that the emission should have a spectral index of 3.75. However, numerous recent observational studies of protostars have found α < 3.75 over a variety of spatial scales (e.g., Kwon et al 2009;Melis et al 2011;Shirley et al 2011;AMI Consortium et al 2012;Tobin et al 2013). In an extreme example, Tobin et al (2013) measured α = 2 between 3.4 and 0.87 mm over baselines ranging from 10 -500 kλ, implying a flat dust opacity law (β = 0).…”
Section: Dust Opacity Lawmentioning
confidence: 99%
“…However, it is also possible that higher values of β are actually caused by the growth of icy mantles on dust grains (e.g., Schnee et al 2010a, and references therein), but this seems to contradict the chemical features discussed earlier. Conversely, observational results of small values of β are often interpreted to be indicative of grain growth (e.g., Testi et al 2003;Draine 2006;Kwon et al 2009). For example, Kwon et al (2009) found that for their sample of Class 0 sources β 1, implying larger grain sizes due to gas accretion and/or coagulation.…”
Section: Dust Propertiesmentioning
confidence: 99%